2015
DOI: 10.2298/jas1502119a
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic divergence for morphological and yield-related traits among some genotypes of durum wheat under drought stress and non-stress conditions

Abstract: Drought stress is the most important factor restricting crop production in the majority of agricultural fields in the world. Durum wheat is generally grown in arid and semi-arid areas and drought often causes serious problems in its production. Fourteen durum wheat genotypes were evaluated under semi-arid Mediterranean climatic conditions in two non-stressed and water-stressed conditions. Data on fourteen agronomic traits are presented to assess the phenotypic diversity and to investigate the relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Lapuimakuni et al (2018) showed YI and HM as the best indices in determining the droughttolerance level of foxtail millet in field conditions. Utilization of tolerance indices is useful to evaluate genotypes' performances under non-stress and stress conditions (Afrooz et al 2021). Combining molecular markers related to stress tolerance traits and tolerance indices might increase the tolerance estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Lapuimakuni et al (2018) showed YI and HM as the best indices in determining the droughttolerance level of foxtail millet in field conditions. Utilization of tolerance indices is useful to evaluate genotypes' performances under non-stress and stress conditions (Afrooz et al 2021). Combining molecular markers related to stress tolerance traits and tolerance indices might increase the tolerance estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Possible segregations in morphological traits are essential for genetic improvement programs and genetic diversity of durum wheat genotypes could be evaluated using morphological variation (De Vita et al, 2010) [12] . Description of the morphological traits has been used for genetic diversity analyses and cultivar development (Gohar et al, 2015) [21] . Genetic variability among durum wheat genotypes can be estimated based on qualitative and quantitative traits.…”
Section: ~ 43 ~mentioning
confidence: 99%
“…Leilah and Khateeb, (2005) [28] reported that the first two principal components PC1 and PC2 accounts for the maximum variability in the data with respect to succeeding components. The character contributing the maximum to the divergence should be given greater emphasis for deciding the type of cluster for purpose of further selection and the choice of parents in hybridization (Jagadev et al, 1991) [22] . Differentiation of the accession into different clusters provides the cumulative effect of a number of characters rather than the contribution of specific few characters.…”
Section: Cluster Mean Analysismentioning
confidence: 99%